Simultaneous Determination of Iron and Copper in Ethanol Fuel Using Nafion/Carbon Nanotubes Electrode - Silva, Josiel J. [UNESP]; Paim, Leonardo L. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Wiley-Blackwell, 2014)
This work presents the analytical method development for iron and copper determination in ethanol fuel. This method was developed using stripping voltammetry with a glassy carbon electrode modified with Nafion/Carbon-nanotubes. With linear sweep stripping voltammetry was achieved a limit of detection of 7.1 x 10(-7) mol L-1 for Fe3+ and 5.1 x 10(-8) mol L-1 for Cu2+. The amperometric sensitivities were 2.0 x 10(6) mu A mol(-1) L for Fe3+ and 2.8 x 10(7) mu A mol(-1) L for Cu2+. The recovery study showed that the method has good accuracy and repeatability, with recovery of 108 and 103% for Fe3+ and Cu2+ respectively.
Keywords: Stripping voltammetry; Iron; Copper; Ethanol fuel; Nafion; Carbon nanotubes